Determining the Beginning of Prayer Times: Qur’an, Hadith, and Scientific Perspectives - Avrilia Aurelia Avissa; Eka Widiya Fradinda; Devia Junita Nur Latipah; Meutya Eka Winanti; Zahra Aulia Suwandi (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Although the determination of the beginning of prayer times has been clearly indicated in the Qur’an and Hadith, these sources primarily provide normative and descriptive guidance without offering precise technical parameters for accurate calculation in diverse geographical contexts. This gap has led to variations in practice and the need for a more systematic approach that integrates religious texts with scientific principles. This study aims to analyze and compare methods for determining the beginning of prayer times from the perspectives of the Qur’an, Hadith, and modern science. Using a descriptive qualitative approach, this research is based on library research by examining classical Islamic texts, contemporary scholarly works, and scientific literature related to astronomical calculations. The findings show that the Qur’an and Hadith emphasize direct observation of natural phenomena, particularly the position of the sun and the formation of shadows, as the primary basis for determining prayer times. In contrast, the scientific approach maintains these scriptural foundations while applying systematic calculations to achieve greater accuracy and consistency. From a scientific perspective, the determination of prayer times relies not only on textual interpretation but also on astronomical and geographical factors, especially solar declination and the equation of time. This study contributes to the discourse on Islamic worship practices by demonstrating that the integration of scriptural guidance and scientific calculation is essential for ensuring accurate, practical, and contextually relevant determination of prayer times in the modern world